Sensory and physicochemical evaluation of suya produced from various round muscles (2016)
A study was conducted to evaluate Suya produced from various round muscles (Rectus femoris, Semi-tendinosus, Biceps-femoris, Semi membranosusand Vastus lateralis) for organoleptic and physiochemical properties. The study was carried out using a completely randomized design. The result from the experiment showed that the fat content was not significantly (P>0.05) affected by the muscle types. The score for overall acceptability on a five point hedonic scale indicated that the consumers preferred Bicepsfemoris which was significantly (P< 0.05) different from other round muscles. Water holding capacity was observed to have influence on other qualities such as flavor, juiciness and tenderness. Product yield was lowest (70.20%) in Vastuslateralis, indicating a good yield from all muscles. It was concluded that the prime cuts, apart from resulting in Suya with high prices are not necessarily better than Suya from less choice parts of the carcass (Rectus femor is, Semi-tendinosus, Biceps-femoris, Semi membranosus and Vastus lateralis) in terms of product yield and eating qualities.